Institutional analysis of strategic choice of micro, small, and medium enterprises a conceptual framework - Roxas, Hernan G.; Lindsay, Val; Ashill, Nicholas; Victorio, Antong (The Philippine Review of Economics, 2007)
A conceptual framework is presented showing formal and informal institutions and their relationship with the strategic choice of micro, small and medium enterprises (MSMEs) in a developing-country setting. Emphasis is placed on how institutions at the subnational level (such as a region or city) influence the strategic orientations of MSMEs in the wake of decentralization, which grants subnational government authorities more political, economic, fiscal, and administrative powers. Furthermore, the paper sheds light on the environmental (institutional) determinism-organizational (strategic) choice nexus. It offers propositions, questions, and issues worth pursuing in future empirical investigations.